A COMPARISON OF TIDAL AND INCENTIVE BREATH COLLECTION METHODS FOR THE DETERMINATION OF BREATH VOLATILES CONCENTRATION. Issue 12 (23rd November 2015) - Anderson, K; Coats, T; Monks, P; White, I; Pandya, H; Beardsmore, C; Skinner, J
Abstract : Objectives & Background: Exhaled Volatile Organic Compounds (eVOCs) have been used to identify patients with many diseases including pseudomonas infection and lung cancer. Breath for eVOC analysis is conventionally collected from one or more deep exhalations. The long controlled exhalation of the American Thoracic Association nitric oxide protocol has been the commonest method used in breath research. However, some patients may be unable or unwilling to perform deep exhalations. Movement of breath analysis from the laboratory to the bedside requires a patient-friendly method for collecting breath samples, especially if breath analysis is to be tested in the relatively uncontrolled environment of an Emergency Department. Continuous monitoring of VOC spectra throughout the breath cycle during tidal breathing has the potential to provide an easier method of sample collection in the clinical situation. This study was designed to compare single controlled exhalation with tidal breathing. Methods: Exhaled breath volatile organic compounds were measured to compare two methods of breath collection in emergency care; the standard single prolonged exhalation (incentive test) and relaxed breathing (tidal test). 125 patients with minor conditions were recruited from the Emergency Department and samples were collected in real-time using an on-line PTR-ToF-MS coupled to Loccioni breath collection apparatus. A Matlab program was used to extract the spectra of the alveolar portion of breath and measure the abundance of each eVOC. Results: The total amount of eVOCs detected by the two methods was highly correlated (R2=0.91), with the incentive method giving slightly higher overall eVOC levels than the tidal breath method (mean of differences=98, 749 NCPS, P<0.0001). Although the total VOCs were highly correlated, there was a large amount of unexplained variation in the spectra. The tidal breath test had a much higher completion (99% compared with 75% for the incentive test), which was due to the greater reliability (less complex sampling equipment) and greater ease of use by patients. Conclusion: Following this study we recommend the use of a tidal breath sampling method in future studies of emergency care patients to prevent selection bias.